Second report on the copper smelting site HLO1 in Wādī al-Ḥilo (Sharjah, UAE) - Kutterer, Johannes; Neureiter, Christina; Jasim, Sabah A. (Proceedings of the Seminar for Arabian Studies, 2013)
Recent fieldwork at site HLO1 in Wādī al-Ḥilo (Sharjah, UAE) — excavated by a joint project of the Directorate of Antiquities of Sharjah and the University of Tübingen (Germany) since 2007 — provides new insights into early mining and smelting processes. The site was used for this purpose from the Early Bronze until the Iron Age. A chronological sequence could be established through pottery studies, which is supported by radiocarbon dates. The workshop area provided evidence for the processing of copper ore, from initial enrichment to the final product in the form of a bun-shaped ingot. A concentration of pitted crushing stones in younger layers may not only be the result of continued ore processing but could also indicate the reprocessing of old slag.